HUBUNGAN PENGGUNAAN SMARTPHONE DENGAN KEJADIAN INSOMNIA PADA MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Siringoringo, Daniel Sulung Utama; Juhanna, Indira Vidiari; Wahyuni, Nila; Dinata, I Made Krisna (E-Jurnal Medika Udayana; Vol 13 No 3 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i03.P17, 2024)
Background : Smartphones are not only used as a communication tool, smartphone have become inseparable from human life around the world. Smartphone usage is always increases. The Central Statistics Agency of Indonesia noted that in 2018 as many as 62.41% of the Indonesian had used mobile phones and mobile phone users in Indonesia increases 3% per year. Beside the positive effects, smartphones also have many negative effects if used excessively. One of the negative effects of excessive smartphone use is insomnia. Aim : Knowing the relationship between smartphone use and the incidence of insomnia among students of Faculty of Medicine, Udayana University. Methods : The method used in this study was an analytical cross-sectional study. Samples selected using simple random sampling method, there are 79 respondents participated in this study and the questionnaires distributed with google form. The data were processed and tested for analysis using the chi-square method. Results : After going through the process of exclusion and drop out, the final number of samples was 75. From 75 samples, 35 samples (46.7%) use smartphone excessively, and 25 samples (33.3%) have insomnia. The results of the bivariate analysis showed a significant relationship between smartphone use and the incidence of insomnia among students of Faculty of Medicine, Udayana University (p = 0,014). Conclusion : There is a relationship between smartphone use and the incidence of insomnia among students of Faculty of Medicine, Udayana University (p = 0,014).   Keywords : Smartphone, Insomnia, Medical Students